Acute lower extremity arterial thrombosis associated with nephrotic syndrome in adults: case series and literature review - Xinqiang Han; Peng Zhao; Zhu Wang; Xingang Ji; Mengpeng Zhao (BMC Nephrology, 2023)
Abstract Background Nephrotic syndrome (NS) is a condition associated with hypercoagulability. Thromboembolic events are a well-recognized complication of NS. Venous thrombosis is well known, while arterial thrombosis, which is more severe, occurs less frequently and is mainly reported in children in the literature. The aim of this study was to understand these rare adult cases of NS associated with acute lower extremity arterial thrombosis and draw attention to them to prevent misdiagnosis and delayed treatment. Methods From January 2011 and October 2022, we conducted a retrospective study of patients with NS and arterial thrombosis. Their clinical manifestations, imaging characteristics, treatments and outcomes were analyzed and compared, and a literature review was performed. Results Nine adults with NS and acute lower limb arterial thrombosis were described. In seven of these patients, six had fresh thrombi that preceded the NS diagnosis, while one had a history of NS for 14 years and previously underwent an emergency thrombectomy. Three of the seven patients eventually underwent above-knee amputations, and the other four underwent arterial revascularization with satisfactory recovery of lower-extremity perfusion. In addition to the seven patients mentioned above, the other two received successful anticoagulant treatment, as the thrombosis was present only in the popliteal artery. Conclusion Acute lower extremity arterial thrombosis is a rare but serious and potentially lethal complication in patients with NS, and early recognition and appropriate management are crucial for good patient outcomes.